Integrated analysis of single-cell and bulk RNA-seq reveals MAGEA3/6-associated immune subtypes and key immune genes in gastric cancer - Linen Li; Hao Chen; Feng Zhou; Yanqing Shi (PLoS ONE, 2025)
The immune microenvironment is critical in gastric cancer (GC), yet epithelial-specific genes linked to immune infiltration remain poorly defined. We integrated single-cell RNA-seq (GSE112302) and TCGA-STAD data to identify epithelial-related differentially expressed genes (DEGs). MAGEA3 and MAGEA6 were selected to classify immune subtypes. Immune infiltration was analyzed using ESTIMATE, CIBERSORT, ssGSEA, and Xcell. WGCNA and survival analysis identified prognostic immune-related genes. MAGEA3/6-high tumors showed low immune infiltration, defining an immune-cold subtype, while MAGEA3/6-low tumors were immune-hot. Further analysis confirmed that BCL11B and PAEP expression levels were significantly associated with immune cell infiltration and immune regulatory activity. MAGEA3/6 expression defines immune subtypes in GC and highlights potential targets for immunotherapy.